Treatment failure with propranolol for subglottic haemangioma. Issue 5 (13th May 2019) - Liu, Zhaobo; Yeo, Yen Huan; Jackson, Conor; Trimble, Keith
Abstract : The use of propranolol for the treatment of subglottic haemangioma has become hugely popular due to its effectiveness and safety profile. We report a case of 7-month-old boy who presented with stridor and histopathology suggestive of subglottic haemangioma following microlaryngoscopy and bronchoscopy (MLB). However, he did not respond to propranolol treatment. This could be due to an older age of propranolol commencement. In general, early commencement of propranolol is necessary when diagnosis of symptomatic infantile haemangioma is made to achieve maximal improvement in symptoms and prevent further proliferation. There should be a high index of suspicion for subglottic haemangioma in children presenting with chronic biphasic stridor, with early MLB and diagnosis. This will allow early treatment, giving the best chance to avoid our situation.